PENINGKATAN MINAT BELAJAR BAHASA (INGGRIS DAN INDONESIA) BAGI SISWA SEKOLAH MENENGAH KEJURUAN 1 KOTA SERANG - Hayati Nupus; Fitri Puspasari; Nilam Pratiwi,; Novi Susanti; Muhamad Iqbal Al - Hifdi (Teknik Mesin ,Universitas Pamulang Serang, 2024)
This community service was conducted to develop students' language competence among Vocational High School students. The students chosen were class XII students with the consideration that they would complete the learning process at school and plunge into society by utilizing their skills. The community service partners are Class XII students of SMK Negeri 1 Kota Serang. From the situation analysis carried out, it appears that the problem faced by partners is that class students lack motivation to learn because of the basic assumption that English is a difficult subject, with the Indonesian language commonly used also being less guarded because they still use their respective regional languages even though they live in a metropolitan area in the middle of the city of Serang. However, from the counseling carried out from this community service activity, the ability to express opinions or messages actively from the material presented with service treatments that motivate to regrow interest in learning languages (English and Indonesian) is very focused and independent, and good. The contributions and benefits obtained by the target audience are motivation to learn from reading comprehension and counseling from the material So that the purpose of this community service activity is one of the lecturer's moments in improving the quality of education in contact with language, especially the implementation is related to fostering the use of foreign languages (English) and Indonesian. Keywords : Increased interest, language learning, communication, service treatment